Increasing astrogenesis in the developing hippocampus induces autistic‐like behavior in mice via enhancing inhibitory synaptic transmission. Issue 1 (9th September 2021) - Chen, Juan; Ma, Xiao‐Lin; Zhao, Hui; Wang, Xiao‐Yu; Xu, Min‐Xin; Wang, Hua; Yang, Tian‐Qi; Peng, Cheng; Liu, Shuang‐Shuang; Huang, Man; Zhou, Yu‐Dong; Shen, Yi
Abstract: Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental disorder characterized primarily by impaired social communication and rigid, repetitive, and stereotyped behaviors. Many studies implicate abnormal synapse development and the resultant abnormalities in synaptic excitatory–inhibitory ( E / I ) balance may underlie many features of the disease, suggesting aberrant neuronal connections and networks are prone to occur in the developing autistic brain. Astrocytes are crucial for synaptic formation and function, and defects in astrocytic activation and function during a critical developmental period may also contribute to the pathogenesis of ASD. Here, we report that increasing hippocampal astrogenesis during development induces autistic‐like behavior in mice and a concurrent decreased E / I ratio in the hippocampus that results from enhanced GABAergic transmission in CA1 pyramidal neurons. Suppressing the aberrantly elevated GABAergic synaptic transmission in hippocampal CA1 area rescues autistic‐like behavior and restores the E / I balance. Thus, we provide direct evidence for a developmental role of astrocytes in driving the behavioral phenotypes of ASD, and our results support that targeting the altered GABAergic neurotransmission may represent a promising therapeutic strategy for ASD. Main Points: Increasing hippocampal astrogenesis during development induces autistic‐like behavior and reduced E / I ratio via enhancing GABAergic inhibition. Suppressing the aberrantly enhanced GABAergic inhibition in CA1 rescues autistic‐like traits.